Antibiotic Prescribing Habits of Dental Surgeons in Hyderabad City, India, for Pulpal and Periapical Pathologies: A Survey. (26th September 2013) - Kumar, K. Pavan; Kaushik, Mamta; Kumar, P. Udaya; Reddy, M. Shilpa; Prashar, Neha
Abstract : Aim . To determine the antibiotic prescribing habits for pulpal and periapical pathology among dentists in Hyderabad city, India. Methodology . A total of 246 questionnaires were distributed to all the dentists registered with the local dental branch. Demographic details and questions regarding type and dosage of antibiotics prescribed for allergic and nonallergic patients were recorded. Inferential statistics were performed, andP < 0.05 was considered statistically significant. Results . The response rate for the study was 87.8%. Around 148 (68.5%) of respondents regularly prescribed antibiotics for endodontic management. The first antibiotic of choice for patients with no history of medical allergies was a combination of amoxicillin and metronidazole, followed by amoxicillin alone (29.1%). The first antibiotic of choice in case of allergy to penicillin was erythromycin. Necrotic pulp with acute apical periodontitis with swelling and moderate/severe preoperative symptom was the condition most commonly identified for antibiotic therapy (92.1%). Conclusion . The present study reveals that the overall antibiotic prescribing practices among this group of dentists were quite high, and there is a need for more educational initiatives to rationalize the use of antibiotics in dentistry.